Advances in Flexible Metallic Transparent Electrodes (Small 19/2022). Issue 19 (12th May 2022) - Nguyen, Viet Huong; Papanastasiou, Dorina T.; Resende, Joao; Bardet, Laetitia; Sannicolo, Thomas; Jiménez, Carmen; Muñoz‐Rojas, David; Nguyen, Ngoc Duy; Bellet, Daniel
Abstract : Metal‐Based Transparent Electrodes In article number 2106006, Viet Huong Nguyen and co‐workers review recent progress and remaining challenges in metallic nanostructure‐based transparent electrodes (TEs), including oxide/metal/oxide multilayers, metal grids, metal nanowire/nanofiber/nanotrough percolating networks, metal meshes based on cracked templated, dealloyed ultrathin metallic films, and some important nanocomposites. The various fields in which metal‐based TEs have been successfully applied as well as emerging and potential applications are summarized.